Effects of Oral Exposure Duration and Gastric Energy Content on Appetite Ratings and Energy Intake in Lean Men - Wijlens, Anne G. M. (Nutrients, 2016)
Studies show that longer oral exposure to food leads to earlier satiation and lowers energy intake. Moreover, higher energy content of food has been shown to lead to higher satiety. Up to now, it has not been studied systematically how oral exposure duration and gastric energy content interact in satiety regulation. Thirty-seven men (22 ± 4 years, 22 ± 2 kg/m(2)) participated in a randomized cross-over trial, in which we independently manipulated: (1) oral exposure duration by modified sham feeding (MSF) for 1 or 8 min; and (2) energy content of gastric load (GL) by a nasogastric tube: 100 kcal/500 mL or 700 kcal/500 mL. Outcome measures were appetite ratings and subsequent energy intake from an ad libitum meal. Energy intake was 35% lower after the GLs with 700 kcal than with 100kcal (p < 0.0001). All appetite ratings were lower in the 700 kcal than in the 100 kcal treatments (area under the curve (AUC); p-values ≤ 0.002); fullness was higher and prospective consumption was lower in the 8 min than in the 1 min MSF treatments (AUC; p-values ≤ 0.02). In conclusion, the current showed that a GL of 700 kcal/500 mL vs. 100 kcal/500 mL increased satiety and lowered energy intake. No additional effects of oral exposure duration could be observed, presumably due to the high contrast in energy between the manipulations. Future research should also focus on the role of oral exposure as such and not only the duration.